2018
DOI: 10.1002/prp2.428
|View full text |Cite
|
Sign up to set email alerts
|

14,15‐epoxyeicosatrienoic acid produced by cytochrome P450s enhances neurite outgrowth of PC12 and rat hippocampal neuronal cells

Abstract: Polyunsaturated fatty acids, such as arachidonic acid, are accumulated in brain and induce neuronal differentiation. Arachidonic acid is metabolized to epoxyeicosatrienoic acids (EETs) and hydroxyeicosatetraenoic acids (HETEs) by cytochrome P450s. In this study, we found that 14,15‐EET and 20‐HETE‐enhanced NGF‐induced rat pheochromocytoma PC12 cell neurite outgrowth even at the concentration of 100 nmol L−1. LC‐MS analysis revealed that 14,15‐EET was effectively produced from arachidonic acid by rat CYP2C11, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Consequently, blockade of BDNF-TrkB signaling ablates the protective effect of sEH genetic deletion in middle cerebral arterial occlusion (MCAO) models of stroke [31,32]. In addition to the protective effects of EETs through their actions on auxiliary cells, EETs are directly able to elicit effects in neurons including growth of neurites [34,35]. These effects suggest sEH inhibition may reduce CNS injury both by reducing the inflammatory response in resident immune cells and by direct neuro-protective effects on the neurons.…”
Section: Neuro-inflammation Induced By Acute Injurymentioning
confidence: 99%
“…Consequently, blockade of BDNF-TrkB signaling ablates the protective effect of sEH genetic deletion in middle cerebral arterial occlusion (MCAO) models of stroke [31,32]. In addition to the protective effects of EETs through their actions on auxiliary cells, EETs are directly able to elicit effects in neurons including growth of neurites [34,35]. These effects suggest sEH inhibition may reduce CNS injury both by reducing the inflammatory response in resident immune cells and by direct neuro-protective effects on the neurons.…”
Section: Neuro-inflammation Induced By Acute Injurymentioning
confidence: 99%
“…A lipid precursor, arachidonic acid (AA) can be metabolized into families of biologically active mediators through CYP450 pathway 23,24 . It has been confirmed that various cytochromase P450 were involved in the metabolic process of epoxyeicosatrienoic acid (EET) generated from AA 25 . EET can also reduce the up‐regulation of endothelial cell adhesion molecule induced by cytokines, inhibit the adhesion of lymphocyte to blood vessels, the activation of nuclear factor (NF‐κB) and inhibit the activation of monocyte/macrophage and its subsequent cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 14,15-EET can induce secretion of vascular endothelial growth factor (VEGF) and BDNF to protect the existing neurons during inflammation [ 176 , 216 ]. Apart from the protective effects of EETs through their actions on auxiliary cells, EETs can directly impact neurons, for instance, by enhancing their neurite outgrowth [ 123 , 143 , 178 , 217 ]. In addition, both genetic ablation and pharmacological inhibition of sEH could attenuate the functional and historical deficits in cerebral ischemia by vascular and neural protection [ 218 , 219 ].…”
Section: Ep-pufas and Neuroinflammationmentioning
confidence: 99%